Rate and abundance - Kiss, Miklós (Journal of Central European Green Innovation, 2021)
Heavy elements (above iron) are formed in neutron capture nucleosynthesis processes. Abundances of these elements can be classified as elemental abundance, isotopic abundance, and abundance of nuclei or individual abundance. It seems worthwhile to investigate the individual abundance of nuclei. This approach allows reading out new information about the abundances that are experienced. What is important and possible to estimate is the neutron density required, to replace the measured abundance of the nuclei, assuming equilibrium processes. This is possible when two stable nuclei are separated by an unstable nucleus. At these places we investigated the neutron density required for the equilibrium nucleosynthesis.Another important question is the possibility of partial formation of the nuclei. We found a mathematical definition for the unified interpretation of when a branching point closes at isotonic case and when it opens at isotopic case. We introduced a more expressive variant for branching, called partial formation rate. With these we are capable of determining the characteristic neutron density values. We found that all experienced nuclei ratios can be obtained at intermediate neutron density (). This occurs e.g., in AGB stars. An important question is the formation of . For this, we identified, that the required neutron density is .The most important quantity during the neutron capture process quantity is the product of the individual abundance and the neutron capture cross section. With this quantity and with the s-nuclei we identify  levels.
Keywords: nucleosynthesis; abundance; neutron density; branching factor; partial formation rate; AGB stars